(untitled) (Research, Society and Development, 2022)
Studies on the occurrence, effect, fate, and removal of drugs from the environment are still scarce in emerging countries. The objective of this study was to evaluate the panorama of studies on the presence of emerging micropollutants of pharmaceutical origin in the surface waters of the countries that make up the BRICS (Brazil, Russia, India, China, and South Africa). Databases and collections in peer-reviewed journals were used, and the queries were refined by evaluating the results of each group individually. In BRICS, knowledge about the levels of contamination and the negative impacts on the aquatic environment by drugs proved to be limited, despite existing studies showing the contamination of surface waters by these pollutants. Thus, these countries need to intensify research and, above all, improve the efficiency of sewage treatment systems. More financial investments are also required in science, as the scarcity of studies in these countries is also related to the high costs of chemical analysis.